A Multi-Method Approach to Inferring Early Agriculturalists' Stone Tool Use at the Crescent Bay Hunt Club Site. Issue 1 (2nd January 2017) - Sterner, Katherine M.; Jeske, Robert J.
ABSTRACT: While there has been much research on the function of stone tools via use-wear analysis, it is clear that a multipronged approach, including an evaluation of material acquisition, production, and tool use, is necessary if tool function is going to prove truly useful for understanding past cultures. Moreover, the role of chipped lithic tools in the economies of agriculture-based populations has seen little research compared to preagricultural systems. A sample of lithic artifacts from the Crescent Bay Hunt Club site, a twelfth- to fourteenth-century Oneota village at Lake Koshkonong in southeastern Wisconsin, are subjected to a multiple-method analysis to determine individual tool use. An assemblage-based analysis provides an overall understanding of the lithic economy. A combination of microscopic identification of edge damage and surface polishes and an analysis of protein residue provides independent lines of evidence that yield strong inferences about tool use in the lithic economies of sedentary agricultural groups in the midcontinent.